In the bed of a duke eaudiobook - Maxwell, Cathy (Cameron Sisters, 2020)
The distressed traveler Charlotte Cameron encounters on a rainy Scottish night is absolutely the worst man she could have invited into her carriage! It is Phillip Maddox, the reprehensible Duke of Colster, who brought the full weight of the ton's fury down upon her—simply because Charlotte encouraged her sister not to wed the powerful peer. And now the seductive devil responsible for her social ruin is sitting close enough to kiss . . . Phillip's distaste for the meddlesome beauty matches Charlotte's—though, under alternate circumstances, he might have enjoyed sampling the sensuous charms of the tempting young chit. There is grave danger, however, on the journey they now must reluctantly share—and a nemesis who means them both mortal harm. But can a passion that inconveniently ignites in the face of disaster erase a painful past . . . and lead two sworn enemies to a most unanticipated destination: the bedchamber? Contains mature themes.